2018
DOI: 10.1111/jiec.12830
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Sustainability‐Based Life Cycle Assessment (ASLCA): A Benchmarking Approach to Operate Agri‐food Systems within the 2°C Global Carbon Budget

Abstract: Given the increasing environmental impacts associated with global agri-food systems, operating and developing these systems within the so-called absolute environmental boundaries has become crucial, and hence the absolute environmental sustainability concept is particularly relevant. This study introduces an approach called absolute sustainability-based life cycle assessment (ASLCA) that informs the climate impacts of an agri-food system (on any economic level) in absolute terms. First, a global carbon budget … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 71 publications
(77 reference statements)
0
28
0
Order By: Relevance
“…In fact, food gained major interest in the current literature asa key driver of environmental impacts (e.g. Springmann et al, 2018 ; Chandrakumar et al, 2019 ). At global level, the food system represented the main driver of climate change, land use, and impacts on terrestrial and aquatic ecosystems, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, food gained major interest in the current literature asa key driver of environmental impacts (e.g. Springmann et al, 2018 ; Chandrakumar et al, 2019 ). At global level, the food system represented the main driver of climate change, land use, and impacts on terrestrial and aquatic ecosystems, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the development of absolute environmental sustainability assessments (AESAs), where, environmental impacts, quantified using LCA, are related to absolute environmental boundaries, such as the PBs. AESA is an emerging field of environmental sustainability assessments (Bjørn et al., 2020) and only a few practical case studies exist (e.g., Algunaibet et al., 2019; Brejnrod, Kalbar, Petersen, & Birkved, 2017; Chandrakumar, McLaren, Jayamaha, & Ramilan, 2019; Ryberg et al., 2018; Wolff, Gondran, & Brodhag, 2017). Nevertheless, results of AESAs offer important added value about the sustainability of the assessed activities relative to absolute environmental boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…The UN has reported that, by 2050, in order to meet the food demand of a projected global population of 9.6 billion, global food production will need to increase by 70 per cent (UN 2013). However, studies have pointed out that, on the global scale, the current food production system is transgressing the environmentally safe operating boundaries in terms of nitrogen use, phosphorus use, biodiversity and land use, and is compromising the global capacity of producing sufficient and nutritious food for the growing population (Willett et al 2019;Springmann et al 2018;Chandrakumar et al 2019;EU 2015;Steffen et al 2015;Rockström et al 2009;Bjørn et al 2020;Poore & Nemecek 2018 halved, and food losses along production and supply chains need to be reduced (UNGA 2015). Also, Goals 14 and 15 are related to our study in terms of calling for sustainable use of terrestrial and marine resources (UNGA 2015).…”
Section: Research Rationale and Conceptual Frameworkmentioning
confidence: 99%
“…As mentioned in the previous section that covers the research rationale, this thesis has demonstrated its major significance in the following aspects: First, this study helps by promoting research methods that could more accurately analyse the energy and material inputs and outputs and environmental impacts of the food systems, and thus helps societies to achieve environmental sustainability goals under the pressure of providing enough nutritiously balanced food for the growing population (Willett et al 2019;Springmann et al 2018;Chandrakumar et al 2019;Steffen et al 2015;Rockström et al 2009). Second, this study addresses the knowledge gap of the interrelationships among environmental sustainability, food systems and diet in the field of sustainability studies.…”
Section: Significance and Innovation Of The Researchmentioning
confidence: 99%
See 1 more Smart Citation